Osteochondroma of the Scapula in a 12-year-old Girl: An Unusual Case Report - Kunne Bharath Raja; K. L. Jagadishwar Rao (Journal of Orthopedics, Traumatology and Rehabilitation)
Osteochondromas are benign bone lesions composed of medullary and cartilaginous bone covered by hyaline cartilage, generally occurring near the growth plate. They are usually solitary and can be sessile or pedunculated. The presence of medullary and cortical bone with the continuity of the tumor is pathognomonic for osteochondroma. We report the case of a 12-year-old girl who was brought to the hospital by her mother with a painful slow-growing mass over the left scapula, with no limitations to the range of movements. On examination, a 4 cm × 3 cm × 4 cm hard, ovoid swelling with irregular margins was noticed and palpated over the dorsal aspect of the scapula. The patient was managed with surgical excision and histopathology confirmed the diagnosis of osteochondroma. Postoperative follow-up, the patient had full range of movements at the shoulder joint without any discomfort. In conclusion, scapular exostoses are rare, and symptomatic patients can be managed with surgical excision of the tumor.